Dairy Goat Farming Development Efforts to Improve the Economy of the Nahdliyin Community in Srumbung District - David Ardiyanto; Rahmad Dwi Ardhiansyah; Ika Nindya Irianti (Lakpesdam PCNU Kota Salatiga, 2025)
Dairy goat farming has strong potential as an economic lever for rural households because it can provide daily cash flow through milk sales. However, increases in farmers’ income are often constrained by productivity variation, limited feed availability and managerial capacity, and weak bargaining power within marketing chains. In the context of the Nahdliyin community in Srumbung District, opportunities for economic strengthening are considered greater because they are supported by relatively established organizational networks and social capital. This study formulates two key questions: (1) how do farmers’ livelihood assets (human, social, financial, physical, and natural capital) influence dairy-goat productivity and enterprise margins; and (2) how can social capital and collective action through NU structures strengthen the value chain (quality–collection–marketing) to improve farmers’ bargaining power and income? The study employs a quantitative-descriptive survey based on records of herd size, estimated milk production, selling price, and daily feed costs, complemented by structured interviews. Analysis was conducted using tabulation and statistical summaries. Complete records from 19 respondents indicate herd sizes of 11–30 head (mean ±17.74) and milk production of 1.0–2.1 liters (mean ±1.65). Assuming a milk price of IDR 18,000/liter and average feed costs of IDR 7,000/head/day, the gross daily margin ranges from IDR 11,000 to IDR 30,800/head/day (approximately IDR 330,000–IDR 924,000/head/month). In conclusion, variations in productivity and margins are primarily shaped by the configuration of livelihood assets especially feed availability, management capacity, production facilities, and working capital while the sustainability of profits depends heavily on marketing efficiency and farmers’ bargaining power. Therefore, productivity gains alone are insufficient without strengthening market institutions. The recommended development approach is a dual-track strategy: (1) strengthening assets and production management (forage plots/feed conservation, training in feeding–health–milking hygiene, and improvements in housing and equipment), and (2) strengthening NU institutions (from branch to sub-district levels) through quality standardization, milk collection points, transparent group governance, and collective marketing/contract partnerships. The diffusion of good practices can be accelerated by leveraging high-performing farmers as early adopters and applying peer-learning mechanisms.